1988
DOI: 10.1111/j.1755-3768.1988.tb04069.x
|View full text |Cite
|
Sign up to set email alerts
|

Status of cyclopentolate as a cycloplegic in children: A comparison with atropine and homatropine

Abstract: Abstract. We compared the cycloplegic effects of cyclopentolate, homatropine and atropine by the retinoscopy findings and residual accommodation left following their use in the same individual. The mean residual accommodation measured after the use of cyclopentolate, homatropine and atropine was 1.48 ± 0.33 D, 2.32 ± 0.37 D and 1.10 D ± 0.28 D, respectively, and the mean difference in retinoscopy readings between cyclopentolate and homatropine, homatropine and atropine, and atropine and cyclopentolate was 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 3 publications
1
14
0
1
Order By: Relevance
“…Atropine is the gold standard for producing cycloplegia; however, due to its complications, the difficult regimen, and prolonged impairment of near vision, has gradually been replaced by cyclopentolate, which has less complications, easier to administer, and has a shorter duration of action. Many authors have demonstrated that the cycloplegic effect of cyclopentolate is comparable to atropine [20,21,30]. Others believe that cyclopentolate alone is not enough in children 2 to 5 years old, especially in esotropic children with hyperopia greater than (2 Diopters) who must be repeatedly refracted with atropine to detect latent hyperopia [9,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atropine is the gold standard for producing cycloplegia; however, due to its complications, the difficult regimen, and prolonged impairment of near vision, has gradually been replaced by cyclopentolate, which has less complications, easier to administer, and has a shorter duration of action. Many authors have demonstrated that the cycloplegic effect of cyclopentolate is comparable to atropine [20,21,30]. Others believe that cyclopentolate alone is not enough in children 2 to 5 years old, especially in esotropic children with hyperopia greater than (2 Diopters) who must be repeatedly refracted with atropine to detect latent hyperopia [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown no significant difference between the cycloplegic effect of cyclopentolate and atropine [20,21]. Inadequate cycloplegia can cause inaccurate refraction and lead to inappropriate diagnostic and therapeutic approaches; on the other hand, over dosage of cycloplegics may cause drug reactions or lead to undue patient discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Atropine is the gold standard for producing cycloplegia; however, due to its complications, the difficult regimen, and prolonged impairment of near vision, it has gradually been replaced by cyclopentolate, which has less complications, is easier to administer, and has a shorter duration of action. Many authors have demonstrated that the cycloplegic effect of cyclopentolate is comparable to atropine (5,6,16). Others believe that cyclopentolate alone is not enough in children 2 to 5 years old, especially in esotropic children with hyperopia greater than 2 D who must be repeatedly refracted with atropine to detect latent hyperopia (10,14).…”
Section: Discussionmentioning
confidence: 99%
“…It incurs fewer complications and has become the drug of choice for cycloplegia (4). Some authors have shown no significant difference between the cycloplegic effect of cyclopentolate and atropine (5,6). No consensus exists on the optimal dosage of cyclopentolate for adequate cycloplegia.…”
mentioning
confidence: 99%
“…One drop of 2% homatropine hydrobromide was instilled in each eye every 10 minutes 6 times. 7,8 Retinoscopy was performed by the use of a streak retinoscope (Heine Optotechnik, Herrsching, Germany) 60 to 90 minutes after instillation of the first drop, followed by automated refraction with a Retinomax 2 handheld automated refractometer (Nikon Inc, Tokyo, Japan). Each eye was read 8 times with the automated refractometer; the average of the results was displayed along with a confidence level from 1 to 10.…”
Section: Methodsmentioning
confidence: 99%